Pathways to Youth Radicalization: A Criminological Analysis of Risk Factors and Prevention Strategies - Fedhli Faisal; Amin Songgirin (Ilomata International Journal of Social Science, 2026)
The growing involvement of youth in violent extremism and radical movements has emerged as a pressing global concern, raising urgent questions about the underlying social and criminogenic factors that drive this phenomenon. This study aims to explore the pathways of youth radicalization through a criminological lens, identifying the key risk factors and proposing context sensitive prevention strategies. Using a normative juridical and descriptive analytical approach, the research examines relevant legal frameworks, criminological theories, and secondary data sources to develop a comprehensive model of youth radicalization. The findings reveal that radicalization is not a linear or homogenous process, but rather the result of intersecting influences such as social marginalization, institutional neglect, identity crises, and exposure to extremist narrative soften reinforced by digital environments. The analysis supports and expands upon strain theory and social disorganization theory, emphasizing the role of structural exclusion and weakened community ties. This study also identifies limitations in dominant counter radicalization strategies that rely heavily on surveillance and psychological profiling, arguing instead for holistic, rights based, and community driven interventions. The research contributes to the theoretical discourse on radicalization while offering actionable recommendations for policymakers, educators, and civil society actors. Its implications underscore the need for preventive frameworks that are ethically grounded, socially inclusive, and empirically informed. By shifting the paradigm from securitization to social resilience, this study advocates for a more just and sustainable approach to addressing youth radicalization.